2021
DOI: 10.3390/genes12071056
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Gene Variants within the COL1A1 and COL5A1 Genes and Musculoskeletal Injuries in Physically Active Caucasian

Abstract: The COL1A1 and COL5A1 variants have been associated with the risk of musculoskeletal injuries. Therefore, the main aim of the study was to investigate the association between three polymorphisms within two genes (rs1800012 in COL1A1, as well as rs12722 and rs13946 in COL5A1) and the reported, yet rarely described in the literature, injuries of the joint and muscle area in a physically active Caucasian population. Polish students (n = 114) were recruited and divided into the following two groups: students with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Another 20 citations were excluded with reasons. Eventually, 21 articles [ 17 , 20 39 ] were enrolled in the meta-analysis.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Another 20 citations were excluded with reasons. Eventually, 21 articles [ 17 , 20 39 ] were enrolled in the meta-analysis.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The basic characteristics of eligible studies were shown in Table 1 . Totally, 21 articles [ 17 , 20 39 ] were included, of which four articles [ 27 , 28 , 31 , 36 ] were cohort studies, one article [ 22 ] was cross-sectional study, and the rest 16 articles were case–control studies. Of the included studies, three studies [ 22 , 28 , 35 ] were on Asian population (Chinese, South Korean, Japanese), one study [ 24 ] was on a mixed population (Brazilian), and the rest 17 studies were on European population.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations